(untitled) (ResearchJet Journal of Analysis and Inventions, 2023)
Ecotourism is a form of tourism which has become comparatively popular in the last few decades. It focuses on promoting responsibility, local conservation efforts, and preserving natural resources. Ecotourism often seeks to provide visitors opportunities to observe and interact with nature without compromising its integrity. This could be through activities such as camping, trekking through ecologically diverse habitats, observing wildlife, bird-watching excursions, or educational tours aimed at raising awareness about unique biospheres or bodies of water like coral reefs. Responsible ecotourism further seeks to benefit locals by flying under eco-friendly initiatives and creating opportunities for them to actively participate in conservation efforts while relying on sustainable business models that don’t leave a significant mark on the environment; potentially protecting it for future generations.